Honey and Cancer: Current Status and Future Directions - Porcza, Laura M. (Diseases, 2016)
Cancer is a leading cause of death worldwide and poses a challenge to treatment. With overwhelming evidence of the role played by diet and lifestyle in cancer risk and prevention, there is a growing interest into the search for chemopreventative or chemotherapeutic agents derived from natural products. Honey is an important source of bioactive compounds derived from plants and recent years have seen an increased interest in its anticancer properties. This review examines the role of honey in targeting key hallmarks of carcinogenesis, including uncontrolled proliferation, apoptosis evasion, angiogenesis, growth factor signalling, invasion, and inflammation. The evidence for honey as an adjunct to conventional cancer therapy is also presented. The review also highlights gaps in the current understanding and concludes that, before translation of evidence from cell culture and animal studies into the clinical setting, further studies are warranted to examine the effects of honey at a molecular level, as well as on cells in the tumour environment.